The Secrets of the Immortal Nicholas Flamel: The Necromancer - Book 4 - Scott, Michael 1959- (New York : Delacorte Press, 2010)
Back in London, twins Sophie and Josh Newman must determine whom they can and cannot trust as they search for Scatty and an immortal who can teach Josh the magic of fire, while Doctor Dee and Machiavelli continue to seek power.
Keywords: Flamel, Nicolas, -- d. 1418 -- Fiction; Machiavelli, Niccolò, -- 1469-1527 -- Fiction; Dee, John, -- 1527-1608 -- Fiction; Alchemy -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Siblings -- Fiction; Twins -- Fiction; London (England) -- Fiction; England -- Fiction